2021
DOI: 10.3390/rel12110914
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Well-Being: Theory, Science, and the Nature Connection

Abstract: The links between spirituality and eudaimonic well-being are examined, beginning with a look at theoretical issues as to whether spirituality is best construed as part of well-being, or as a possible influence on well-being. A brief review of scientific findings from the MIDUS study linking religion and spirituality to well-being and other outcomes is then provided to show recent empirical work on these topics. Suggestions for future work are also provided. The third section is forward-thinking and addresses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Connecting to nature has well-established therapeutic benefits. For instance, exercising in the countryside improves mood [ 9 ], gardening promotes stress recovery [ 10 ], and immersing oneself in nature through activities such as “forest bathing” offers benefits to both mind and body [ 11 ] and can promote feelings of awe, wonder, and spiritual well-being [ 11 , 12 ]. Notably, studies have shown that exposure to specific elements of nature (eg, auditory and visual cues) can also be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Connecting to nature has well-established therapeutic benefits. For instance, exercising in the countryside improves mood [ 9 ], gardening promotes stress recovery [ 10 ], and immersing oneself in nature through activities such as “forest bathing” offers benefits to both mind and body [ 11 ] and can promote feelings of awe, wonder, and spiritual well-being [ 11 , 12 ]. Notably, studies have shown that exposure to specific elements of nature (eg, auditory and visual cues) can also be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Here, a change toward new ways of being self-aware and aware of developing values takes place in the subthemes of spirituality, virtues, personal growth, relation to nature, and holism. The findings add empiric knowledge to the value of wilderness experiences for the development of spiritual well-being ( Ryff, 2021 ). These findings also make sense to earlier research on aesthetic nature experience, where a two-factor model suggested a difference between beauty and the sublime ( Graves et al, 2020 ).…”
Section: Discussionmentioning
confidence: 78%
“…Following Ryff (2021) , the centrality of nature in understanding deeper meanings for what our souls need is critical for our individual and planet’s well-being. Thus, studies of spirituality within wilderness experiences are at the heart of understanding eudaimonia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nature is powerfully present in the visual arts and music as well and has been throughout human history. I have recently covered these topics elsewhere, including nature’s role in nurturing the human spirit ( Ryff, 2021b ) and here highlight some of that work. My overall messages are that those interested in understanding influences that nurture good lives as well as a concern for our planet need to bring encounters with nature into their scientific studies, including interventions designed to promote diverse aspects of well-being and health.…”
Section: Looking Forward: Suggested New Directions For Positive Psych...mentioning
confidence: 99%